Digest: Fitness costs of Spiroplasma infection in pea aphids*. (3rd June 2019) - El‐Deeb, Omar
Abstract: Endosymbionts sometimes help their hosts resist parasites, but does infection of pea aphids ( Acyrthosiphon pisum ) with different strains of the endosymbiont Spiroplasma confer fitness benefits that offset the costs? Mathé‐Hubert et al. found that across four life‐history traits, Spiroplasma infection induced negative effects on host fitness when compared to controls. Only two of 12 strains of Spiroplasma showed a marginal protective effect against host parasitism by Aphidius ervi, implying Spiroplasma infection is almost entirely detrimental to pea aphid host fitness.